Pengaruh Kewibawaan Guru Pai Terhadap Pembinaan Akhlak Siswa di SMK 2 Kota Bengkulu - Kiki Kiki (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The teacher assumes the apostolic task of conveying God's messages to mankind more specifically the duty of the Prophet in relation to education. Therefore, the authority of PAI teachers plays a very important role in fostering student morals. The purpose of this study is to determine whether or not there is an influence of the authority of PAI teachers on the moral development of students. This research is a quantifiable research with the positivism method. The sample in this study was 41 students. Data is collected using questionnaire and documentation techniques. The data from this study were analyzed using the formulas Normality test, Linearity test, and Partial test. From the results of the partial test calculation (t-test), the result of the value of the calculation is 3,001 and the Ttabel value is 2,024 with a significant value of 0.004 with the criteria for calculating the >Ttabel and if the significant value is 0.004 < 0.005, then H0 is rejected so that there is a significant influence between variable X (PAI Teacher Authority) on variable Y (Student Morals) OF SMKN 2 Bengkulu City.